Takarazuka Revue: acting, atmosphere and gender in Japanese musical theater - Aleixo, Daniel Ribeiro Fernandes (Revista Brasileira de Estudos da Presença, 2023)
This article exposes the elements that legitimize the takarazuka musical theater, founded at the beginning of the 20th century, as a performative language. It starts with two shows, Rose of Versailles and Once upon a time in America, highlighting three elements of analysis: acting methodology, scenic atmosphere and gender performance. It infers the subversion of the woman's role as an artist and the negotiation between current gender standards through small reinventions and inherited technical attributes. Takarazuka performativity resorts to artistic and commercial choices that promote the friction and fantasy of genders, in addition to aligning political precepts from the feudal era with modernism.